2017
DOI: 10.20985/1980-5160.2016.v11n4.1150
|View full text |Cite
|
Sign up to set email alerts
|

Aplicação da análise de modo e efeitos de falha para o gerenciamento de riscos de um projeto

Abstract: DestaquesGerenciamento de riscos em novos projetos representa fator importante para a performance de um novo produto, bem como para o sucesso deste novo projeto.Algumas abordagens dentro de gerenciamento de projetos possuem a preocupação de reduzir os riscos existentes de fracasso em novos projetos.Dentre as diversas ferramentas gerenciais para auxiliar no gerenciamento de riscos de novos projetos, tem-se a Análise de Modo e Efeitos de Falha (FMEA - Failure Mode and Effects Analysis).A FMEA é tida como uma fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Still on the calculation of the RPN in the FMEA, mistakes can occur due to the inversely proportional meaning of the classification categories for the probability of detection and occurrence; different scores can originate the same RPN with the risk of not expressing the magnitude of the failure. 19,22 In this way, one of the members should be familiar with the tool of choice in order to lead the others to the correct use and clarification. 20,25 More recent studies have demonstrated the effectiveness of the tools to evaluate work processes and raise the errors that can directly harm patient safety.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Still on the calculation of the RPN in the FMEA, mistakes can occur due to the inversely proportional meaning of the classification categories for the probability of detection and occurrence; different scores can originate the same RPN with the risk of not expressing the magnitude of the failure. 19,22 In this way, one of the members should be familiar with the tool of choice in order to lead the others to the correct use and clarification. 20,25 More recent studies have demonstrated the effectiveness of the tools to evaluate work processes and raise the errors that can directly harm patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…1 It is defined as a qualitative methodology that allows the analysis, in the workflow, of the flaws, their causes and effects, leading to the reflection of actions that allow the early correction of these errors. 19 The FMEA is divided into seven stages: 1) selecting a work process to be evaluated; 2) recruiting a multidisciplinary team for the application; 3) establishing a workflow on the part of the team; 4) raising the inherent flaws in the processes, causes and effects; 5) for each failure, calculating the Risc Priority Number (RPN); 6) evaluating the flaws with higher RPN and defining the practical actions and 7) recalculating the RPN after the implementation of improvement actions. 20,21 To select a work process, one must prioritize that which stands out for its greater observance of failures.…”
Section: Failure Mode and Effects Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…e research proposed a quantitative risk assessment (QRA) method of risk management in the urban area sector. Later, an improved QRA model to quantify risks for nonhomogenous urban growth was designed, since the current QRA models for commercial construction are irrelevant, which was proposed by Meng et al [16]. Many authors used the probability method for construction risk in the last decade such as Monte Carlo [1], event tree analysis [6,14,15], failure mode and effect analysis [16], risk matrix [17], and multicriteria decision-making [1].…”
Section: Related Work In the Risk Assessment Methodsmentioning
confidence: 99%